Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
https://www.feministeconomics.net
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Les femmes et le marché du travail au Québec : portrait statistique - Ruth, Rose (Service aux collectivités de l'UQAM/Comité consultatif Femmes en développement de la main-d'oeuvre/Conseil d'intervention pour l'accès des femmes au travail, 2013)
« L'objectif de cette étude, effectuée par l’économiste Ruth Rose, professeure associée à l’Université du Québec à Montréal, est de présenter un portrait statistique de la situation des femmes québécoises sur le marché du travail, de son évolution au cours des années récentes et de la comparer à celle des hommes, en tenant compte de la diversité de la population féminine. » (2013, 1)
Mise à jour de l'étude publiée en 2005 et intitulée Les femmes et le marché de l'emploi, la situation économique et professionnelle des Québecoises, réalisée par le Comité consultatif Femmes en développement de la main-d'oeuvre. https://biblio.cdeacf.ca/cgi-bin/koha/opac-detail.pl?biblionumber=222101&query_desc=Les%20femmes%20et%20le%20marché%20du%20travail%20au%20Québec%20%3A%20portrait%20statistique
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; amériques; approches et analyses; discipline; périodes historiques; québec; rapports sociaux de sexe; recherche partenariale; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; travail; économie